2012
DOI: 10.5142/jgr.2012.36.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hydrogen Sulfide-induced Angiogenesis and Inflammation in Vascular Endothelial Cells: Potential Mechanisms of Gastric Cancer Prevention by Korean Red Ginseng

Abstract: Previously, we reported that Helicobacter pylori-associated gastritis and gastric cancer are closely associated with increased levels of hydrogen sulfide (H2S) and that Korean red ginseng significantly reduced the severity of H. pylori-associated gastric diseases by attenuating H2S generation. Because the incubation of endothelial cells with H2S has been known to enhance their angiogenic activities, we hypothesized that the amelioration of H2S-induced gastric inflammation or angiogenesis in human umbilical vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
1
18
0
2
Order By: Relevance
“…NaHS was shown to reduce oxLDL-induced foam cell formation in macrophages and TNF-α-stimulated ICAM-1 expression in HUVECs (Zhao et al 2011;Wang et al 2013b). In contrast, Choi et al showed that Korean red ginseng extracts inhibit the expression of inflammatory mediators, including IL-8 and IL-6, via reduced CSE expression and H 2 S production in ECs (Choi et al 2012). Supplement of exogenously applied H 2 S reversed the Korean red ginseng extract-improved inflammation status in ECs.…”
Section: H 2 S and Ec Inflammationmentioning
confidence: 99%
“…NaHS was shown to reduce oxLDL-induced foam cell formation in macrophages and TNF-α-stimulated ICAM-1 expression in HUVECs (Zhao et al 2011;Wang et al 2013b). In contrast, Choi et al showed that Korean red ginseng extracts inhibit the expression of inflammatory mediators, including IL-8 and IL-6, via reduced CSE expression and H 2 S production in ECs (Choi et al 2012). Supplement of exogenously applied H 2 S reversed the Korean red ginseng extract-improved inflammation status in ECs.…”
Section: H 2 S and Ec Inflammationmentioning
confidence: 99%
“…NaHS was shown to reduce oxLDL-induced foam cell formation in macrophages and TNF-α-stimulated ICAM-1 expression in HUVECs Wang et al 2013b). In contrast, Choi et al showed that Korean red ginseng extracts inhibit the expression of inflammatory mediators, including IL-8 and IL-6, via reduced CSE expression and H 2 S production in ECs (Choi et al 2012). Supplement of exogenously applied H 2 S reversed the Korean red ginseng extract-improved inflammation status in ECs.…”
Section: H 2 S and Ec Inflammationmentioning
confidence: 93%
“…사포닌의 화학구조는 크게 당부분(glycone)과 비당부 분(aglycone)으로 구성된 배당체(glucoside)이다. 사포 닌은 항산화 작용이 뛰어나며 면역력을 증강시키고 항염 효과 등이 있는 것으로 알려져 있다 [3][4][5][6]. 이러한 배당체가 체내로 흡수될 때에는 장내 특유 미생물에 의해서 분해되어 흡수되는 것으로 알려져 있다 [7,8].…”
Section: 서 론unclassified